Theoretical physicist Brian Greene - Doeden, Matt (Minneapolis Lerner Publications Company, 2015)
Brian Greene's father taught him to look at the world in different ways. Years later, he started helping others understand the universe from new perspectives. Learn how Brian became a physics expert and bestselling author
A new perspective -- Big ideas -- A broader audience -- Science superstar
Includes bibliographical references (page31) and index
Hurg
5 18 22
Keywords: Physicists -- United States -- Biography